MOTIVASI DAN KETAHANAN PSIKOLOGIS MAHASISWA RANTAU DARI LUAR KALIMANTAN BARAT DI UNIVERSITAS SULTAN MUHAMMAD SYAFIUDDIN SAMBAS - Firli Ariska; Nurysahira; Erzira; Syafaria (Tarbiya Islamica, 2026)
This study aimed to describe the motivation and psychological resilience of out-of-town students during their college years. This study employed a descriptive qualitative approach involving ten out-of-town students from outside West Kalimantan who were studying in Sambas Regency. Data were collected through an online questionnaire using Google Form and analyzed using thematic analysis techniques. The results showed that out-of-town students encountered various challenges, including homesickness, academic pressures and adaptation to a new environment. Nevertheless, the respondents demonstrated strong motivation to achieve their goals, complete their studies on time and make their families proud. Psychological resilience was reflected in their ability to adapt to new a environment, manage academic and emotional pressures and maintain their commitment to completing their studies. Social support from family and peers, as well as the use of positive coping strategies, played an important role in helping students overcome various challenges during their academic journey. The findings also indicated that student’s ability to build positive social reletionships and adapt to diverse environments reflected attitudes of tolerance and balance in social life. Therefore, motivation and psychological resilience are important factors that support the successful adaptation of out-of-town students in higher education.